Maternal Serum Gasdermin D Concentrations in Pregnancies Complicated by Isolated Intrauterine Growth Restriction - Kobal, Berna Buse; Kale, İbrahim; Pektaş, Ahmet Murat; Ozel, Aysegul; Muhcu, Murat (Zeitschrift für Geburtshilfe und Neonatologie, 2022)
Objective We aimed to investigate the relationship between the isolated intrauterine growth restriction (IUGR) and maternal serum gasdermin D (GSDMD) concentration.Materials and methods This cross-sectional study was conducted with 80 pregnant women who applied to the Umraniye Training and Research Hospital Gynecology and Obstetrics Clinic between January 2022 and May 2022. The IUGR group consisted of 40 pregnant women diagnosed with IUGR in the third trimester, and the control group consisted of 40 healthy pregnant women matched with the IUGR group in terms of age and BMI. Demographic characteristics, ultrasound findings, and neonatal outcomes were noted. The two groups were compared in terms of maternal serum GSDMD concentrations.Results Both groups were similar in terms of demographic characteristics. Fetal biometric measurements were found to be significantly lower in the IUGR group compared to the control group, and umbilical artery Doppler PI and SD were found to be higher. Gestational age, newborn birth weight, birth height, and Apgar scores were significantly lower and NICU admission rate was higher in the IUGR group. Gestational age at blood sampling for GSDMD was similar in both groups (p=0.805). While maternal serum GSDMD concentration was 11.14 ng/ml in the IUGR group, it was 6.66 ng/ml in the control group (p=0.000). ROC analysis was performed to determine the value of GSDMD concentration in terms of IUGR estimation. AUC analysis of GSDMD for IUGR estimation was 0.88 (p<.001, 95% CI=0.80–0.95). The optimal cutoff value for GSDMD concentration was determined as 8.84 ng/ml with 80% sensitivity and 75% specificity.Conclusion Maternal serum GSDMD concentrations were found to be higher in pregnant women whose pregnancy was complicated by isolated IUGR. We think that high GSDMD concentrations may be a reflection of increased GSDMD-mediated pyroptosis in placental tissue in isolated IUGR cases.
Keywords: intrauterine growth restriction; gasdermin D; placenta; pyroptosis